WEANING TO ESTRUS INTERVAL OF SOWS REARED UNDER FIELD CONDITION OF AIZAWL (Indian Journal of Animal Production and Management, 2013)
A total of 29 sows (14 LWY, 7 HS and 9 BB) sows were studied for a period of 11 months under the field condition of Aizawl district, Mizoram. The average weaning to estrus interval (WEI) of sows was found to be 13.52±3.35 days. The WEI in Large White Yorkshire, Hampshire and Burmese Black was found to be 17.43±6.24, 7.67±0.49 and 12.00±5.21 days respectively. However, there was non-significant difference among the three breeds i.e Large White Yorkshire (LWY), Hampshire (HS) and Burmese Black (BB).
Keywords: Weaning to estrus interval; sows; field condition